Green tea (Camellia sinensis) leaf extract maintained spermatozoa plasma membrane integrity, viability, and motility of mice (Mus musculus) exposed to cigarette smoke - Maryana Siska Silviani; Moh. Sukmanadi; Rochmah Kurnijasanti; Sri Pantja Madyawati; Epy Muhammad Luqman (Universitas Airlangga, 2022)
Cigarette smoke chemicals caused oxidative stress by increasing Reactive Oxygen Species (ROS). ROS exposure could be neutralized by antioxidants, such as green tea (Camellia sinensis) leaf extract. This study aimed to determine the effect of green tea extract (GTE) on spermatozoa plasma membrane integrity, spermatozoa viability, and spermatozoa motility of mice (Mus musculus) exposed to cigarette smoke. Twenty-five mice were randomly divided into five groups. Group C- mice were given a placebo (1% Sodium carboxymethyl cellulose, Na-CMC). Group C+, T1, T2, and T3 mice were exposed to cigarette smoke and given 0, 20, 40, and 60 mg/kg BW GTE respectively. Cigarette smoke exposure used a clove cigarette per day. GTE in 1% Na-CMC solution was administered at 0.5 mL orally using a gastric probe. The treatment was conducted daily for 36 days, and on day 37, all mice were euthanized for spermatozoa evaluation. The results showed that all parameters evaluated in the C+ group were lower (p <0.05) than in C- group. Administration of GTE in the T2 group increased (p <0.05) all parameters compared to mice in the C+ group. However, administration of GTE to mice in the T3 group caused a decrease (p <0.05) in all parameters than those of the T2 group and was not significantly different (p >0.05) compared to those of the C+ group. It could be concluded that the administration of GTE at 40 mg/kg BW has maintained the spermatozoa plasma membrane integrity, spermatozoa viability, and spermatozoa motility of mice exposed to cigarette smoke.